Glia-Derived Extracellular Vesicles: Role in Central Nervous System Communication in Health and Disease - Pistono, Cristiana; Bister, Nea; Stanová, Iveta; Malm, Tarja (Frontiers in Cell and Developmental Biology, 2021)
Glial cells are crucial for the maintenance of correct neuronal functionality in a physiological state and intervene to restore the equilibrium when environmental or pathological conditions challenge brain homeostasis. The communication between glial cells and neurons is essential and extracellular vesicles (EVs) take part in this function by transporting a plethora of molecules with the capacity of influence the function of recipient cells. EVs, including exosomes and microvesicles, are a heterogeneous group of biogenetically distinct double membrane-enclosed vesicles. These vesicle subtypes are difficult to discern once release from the cell and we will address them with the general term of EVs. This review is focused on EVs secreted by astrocytes, oligodendrocytes and microglia, aiming to shed light on their impact on neuronal functions and their influence on other glial cells. We collect evidence on neuroprotective and homeostatic effects of glial EVs, including neuronal plasticity. On the other hand, current knowledge of the detrimental effects of the EVs in pathological conditions is addressed. Finally, we propose directions for future studies and evaluate the potential of EVs as a therapeutic treatment for neurological disorders.